PROBLEMATIKA UNDANG - UNDANG PERLINDUNGAN KONSUMEN TERKAIT KEPASTIAN HUKUM TERHADAP KEPUTUSAN BADAN PENYELESAIAN SENGKETA KONSUMEN - Varel Tristan Ayub Laiskodat, Varel (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2021)
This study seeks to harmonize public perceptions of ambiguity in contradictory laws in order to promote public insight, particularly among those who may become customers or business actors and who may be able to comprehend the contents of the UUPK during a dispute. contained and as a legal basis for resolving consumer disputes through the Consumer Dispute Settlement Agency in order to avoid future protracted errors. The approach method that could be employed in this The use of research is mandated by law., which would involve an examination of the legislation and case studies. The findings of this study indicate that consumer dispute resolution decisions made by BPSK lack legal certainty due to two major inconsistencies between the consumer protection law's article 54 paragraph 3 (which states that BPSK decisions are final and binding) and the same law's article 54 paragraph.